"I deserve a break!": how temporal landmarks and the perception of deservingness influence consumers' travel motivation and intention. Issue 5 (12th June 2020) - Li, Qing; Yu, Larry
ABSTRACT: This study investigates the impact of temporal landmarks on consumers' travel motivation and intention through three experimental studies. Results demonstrate that being reminded of public and personal temporal landmarks can boost consumers' travel motivation, with the effect driven by consumers' perception of deservingness. The effect of temporal landmarks on travel motivation was shown to be weakened when consumers were confronted with goal conflicts attributed internally to consumers themselves, but not those attributed externally to others. We provide evidence that perceptions of deservingness influence travel intention, and these perceptions are influenced by both temporal landmarks and goal conflicts that are internally attributed.